Corrosion behaviour of poly-l-lactic acid coated magnesium by electrospinning / Wan Nur Atikah Haji Wan Nafi - Wan Nur Atikah, Haji Wan Nafi (2017)
Every year, the rate of accident involving bone fractures increases rapidly and most fractures need to be fixed with surgical bone implants. Most implants are made from medical grade metal such as stainless steel, cobalt, titanium and others. One of the characters of a good short term implant is its ability to be degraded after bones have healed. However, most of the temporary implants are made from non-biodegradable metals. In consequence, magnesium alloys has potential to be used as short term implants due to their ability to degrade in chloride containing solution and properties similar to human bones. However, its high degradation rate limits its clinical applications. This study has introduced an approach to control the corrosion rate of high purity magnesium (HP Mg) and AZ91 by coating them with polymeric membrane of poly-L-lactic acid (PLLA) by electrospinning. An 8 wt % of PLLA was magnetic stirred to dissolve in the chloroform at room temperature. The prepared PLLA solution was then fed into a 10 ml syringe with thin needle. The electrospun coating of PLLA on HP Mg and AZ91 samples were done at feed rate of 1 ml/hr, voltage of 10 kV and distance of 15 cm between the syringe tip and collector. Scanning electron microscope (SEM) and microscratch test were done to characterize the thickness and adhesiveness of the coating on HP Mg and AZ91. In addition ASTM 3359 standard test and surface profiler were also performed to study the adhesiveness and thickness of the coating respectively. The corrosion behaviour of uncoated Mg and Mg coated PLLA samples were studied by immersing them in Hank’s solution for 14 days at human body temperature (37 °C). The pH of Hank’s solution was maintained at 7. The corrosion rate was calculated from evolved hydrogen during the immersion and weight loss after immersion. The surface of the samples before and after immersion was evaluated by scanning electron microscope (SEM). It was observed that PLLA was successfully coated the HP Mg and AZ91 samples. The corrosion rates of HP Mg and AZ91 coated PLLA samples without hole were found lower than uncoated samples. PLLA coating on HP Mg and AZ91 by electrospinning has improved the corrosion resistance by delaying the corrosion initiation. Keywords: Magnesium, PLLA coating, Hydrogen Evolution, Weight loss, SEM.